Optimization of Weighted Aggregated Sum Product Assessment - Zavadskas, E. K.; Turskis, Z.; Antucheviciene, J.; Zakarevicius, A. (Elektronika ir Elektrotechnika, 2012)
One of important parts of every computer-aided multiple criteria decision support system is selection of a proper MCDM (Multiple Criteria Decision Making) method. WSM (Weighted Sum Model) and WPM (Weighted Product Model) are analyzed in the current research. The aim of the research is to measure the accuracy of the latter methods and to propose a method to increase the ranking accuracy of alternatives. It is proposed to apply joint WASPAS (Weighted Aggregates Sum Product Assessment) method. Methodology for evaluation of accuracy, based on initial criteria values, is developed. Optimization of weighted aggregated function is suggested, that enables to reach the highest accuracy of measurement. An example of application of the proposed methodology is presented. Ill. 3, bibl. 15, tabl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1810